Prinsip Keterbukaan Beneficial Owner (BO) Perusahaan Terbuka Terhadap Upaya Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang (TPPU) - Leonard Pandapotan Sinaga; Bismar Nasution; Mahmul Siregar; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. Beneficial owner is every party entitled to and/or receives certain benefits related to the customer's account, is the true owner of funds and / or securities placed on the financial service provider (ultimately own account), controlling customer transactions, providing power to conduct transactions, control corporations or other agreements (legal arrangements), and/or constitute the final controller of transactions made through legal entities or based on an agreement. In common law, ownership terminology is divided into two, namely legal ownership and factual ownership (beneficial ownership), someone who is legally as a legal owner but substantially the owner of the property is someone else because the property doesn't belong to them. Thus, a person who has legal assets is not necessarily the real owner of assets and the actual recipient of the income from the property (the beneficial owner of income). This research is a normative and analytical descriptive research that describes and analyzes the disclosure principle of a beneficial owner (BO) of an open company to prevent and eradicate money laundering crime (TPPU). The results of this study show that the disclosure of a beneficial owner of a public company through financial service providers in the capital market sector may prevent the possibility of being used as a place for perpetrators of money laundering, this is due to the application of the principle of recognizing customers and single investor identification in each transaction. The transparency of beneficial owner from an open company shareholding through the stock exchange to a fund, will narrow the space for the perpetrators of money laundering to hide, save large funds that are allegedly sourced from the proceeds of crime or illegal, so the beneficial owner openness principle could provide preventive measures to perpetrators of money laundering and facilitate law enforcement in eradicating money laundering. Keywords: beneficial owner, public company, money laundering